1976
DOI: 10.1007/bf01933955
|View full text |Cite
|
Sign up to set email alerts
|

3-Hydroxy-3-methylglutaric acid and experimental atherosclerosis in rats

Abstract: In rats 3-hydroxy-3-methylglutaric acid effectively counteracts the lipemic and atherosclerotic response of massive doses of vitamin D2. It regressed the formation of atheromatous arterial lesions. Furthermore the significant decrease in serum beta-lipoprotein levels on HMG treatment could be due to decrease in VLDL triglyceride and cholesterol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

1978
1978
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…23−26 Studies have shown that HMG can induce dose-dependent hypocholesterolemic effects in animal models, including lowering serum lipids in hyperlipidemic rats similar to SDG. 27,28 In the gastrointestinal tract, the copolymer undergoes hydrolysis to release both SDG and HMG. Therefore, both compounds might contribute to the hypercholesterolemic effects of whole ground flaxseed.…”
mentioning
confidence: 99%
“…23−26 Studies have shown that HMG can induce dose-dependent hypocholesterolemic effects in animal models, including lowering serum lipids in hyperlipidemic rats similar to SDG. 27,28 In the gastrointestinal tract, the copolymer undergoes hydrolysis to release both SDG and HMG. Therefore, both compounds might contribute to the hypercholesterolemic effects of whole ground flaxseed.…”
mentioning
confidence: 99%
“…Consistent with such findings was the observation that HMGA could shrink atherosclerotic lesions in male albino rabbits (Lupien et al 1973b); unfortunately, such work appears not to have been done in humans. As well, Yousufzai and Siddiqi (1976b) observed aortic arch atheromatous lesion regression in non-diabetic rats as the result of HMGA administration. Such atherosclerosis management is important as atherosclerosis causes myocardial infarction and stroke the two major causes of death in T2D patients (Sasaki et al 1995;Alberti et al 2007;Sharma et al 2017).…”
Section: Hyperglycemiamentioning
confidence: 62%
“…In silico studies have also highlighted the α-glucosidase inhibitory properties of catechin [ 37 ]. Further attention can be devoted to meglutol or 3-hydroxy-3-methyl glutaric acid, which is known to induce hypoglycemia and to regulate lipid metabolism [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%